Glomerular filtration rate abnormalities in sickle cell disease - Afangbedji, Nowah; Jerebtsova, Marina (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) is a group of inherited blood disorders affecting the β-globin gene, resulting in the polymerization of hemoglobin and subsequent sickling of the red blood cell. Renal disease, the most common complication in SCD, begins in childhood with glomerular hyperfiltration and then progresses into albuminuria, a fast decline of glomerular filtration, and renal failure in adults. This mini-review focuses on glomerular filtration abnormalities and the mechanisms of hyperfiltration, explores genetic modifiers and methods of estimating glomerular filtration rates, and examines novel biomarkers of glomerular filtration in SCD.